2023
DOI: 10.3390/plants12142641
|View full text |Cite
|
Sign up to set email alerts
|

Sicilian Rivet Wheat Landraces: Grain Characteristics and Technological Quality of Flour and Bread

Abstract: In recent years, the growth of tetraploid Sicilian wheat landraces has been arousing increasing interest. In this study, eighteen local genotypes of Triticum turgidum subsp. turgidum, belonging to the groups ‘Bufala’, ‘Ciciredda’, ‘Bivona’ and ‘Paola’, and two cultivars of Triticum turgidum subsp. durum (the old variety ‘Bidì’, and a more recent variety ‘Simeto’) were assessed for the characteristics of the grain and bread-making performance of their flours and doughs, as well as the quality of the loaves. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Such wheat can be an improver for weak bread wheat. Spina et al (2023) found no high our strength genotypes among 20 Sicilian Rivet wheats that were used in ancient times for local traditional bread. A large variability in our strength is also characteristic of durum wheat.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Such wheat can be an improver for weak bread wheat. Spina et al (2023) found no high our strength genotypes among 20 Sicilian Rivet wheats that were used in ancient times for local traditional bread. A large variability in our strength is also characteristic of durum wheat.…”
Section: Discussionmentioning
confidence: 92%
“…In some studies, the variation in vitreousness in durum wheat was in the range of 70-90% (Korkut et al 2007;Alsaleh et al 2019). The percentage of starchy (soft) grains in various Sicilian Rivet accessions ranged from 6 to 72 percent (Spina et al 2023). It has been shown that this trait is highly dependent on growing conditions, in particular, on air humidity during grain ripening (Sandhu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this condition, the photosynthesis rate is reduced by the plant response to lower stomatal conductance with the aim of reducing water transpiration [19,[22][23][24][25][26]. Sicilian wheat landraces have demonstrated to be particularly adapted to non-optimal climatic conditions during anthesis and grain ripening stage and low-input agronomical practices [27,28], while the role of photosynthesis efficiency or stomatal conductance in achieving these results has yet to be assessed.…”
Section: Introductionmentioning
confidence: 99%